Sogug Musical Instrument to Build Musical Intelligence (Rhythm Element) in Early Childhood - Tirtaningsih, Munaisra Tri; Hartono, Hartono; Florentinus, Totok Sumaryanto (Universitas Negeri Semarang, 2018)
Sogug musical instrument is a type of traditional musical instrument, including rhythmic musical instruments from the Kalipare village community, Malang Regency. The research aims to describe how Sogug musical instruments can be used to stimulate rhythm sensitivity and how to apply Sogug musical instruments to children. The method used in this study is a qualitative method with descriptive data exposure. The research subjects of the group are Muslimat NU TK A Kalipare Malang, with observation, interview, and document study data collection techniques. Data validation techniques used in this research is source triangulation and data analysis techniques with data reduction, presentation of data and conclusions. The results showed that the Sogug musical instrument was appropriately used and appropriately applied as an alternative to stimulate early childhood musical intelligence (rhythm). It is because of the instruments and ways to play Sogug musical instruments is in accordance with the early childhood stages of growth, needs, abilities and physical motor development.